Results from AD-HEARING (ADherence to and adjustment of HEARING aids in clinical routine care as preventive dementia strategy): a prospective 6-month follow-up study on cognition and psychological well-being - Belz, Michael; Gmeinwieser, Sebastian; Abdel-Hamid, Mona; Kühler, Robert; Blum, Jenny; Hessmann, Philipp; Strenzke, Nicola; Bartels, Claudia (Frontiers in Psychiatry, 2025)
BackgroundAge-related hearing loss (ARHL) is a modifiable dementia risk factor and often associated with psychological symptoms. Hearing aid use might reduce this risk by preserving cognitive and psychological functions.ObjectiveThis study aims to investigate the influence of ARHL and hearing aid use on cognition and different aspects of psychological well-being.MethodsDuring 05/2021 and 05/2023, 31 subjects with audiometrically confirmed ARHL were included and 28 underwent follow-up 6 months later (final analysis sample). Successful hearing aid adjustment was controlled by fitting protocols, and hearing aid use was self-reported (IOI-SH). The following primary outcomes were analyzed by general linear models (GLM) for repeated measures and compared between hearing aid users (>8 h of daily use) vs. non-users (≤8 h of daily use) at baseline and follow-up: (1) cognition: Consortium To Establish a Registry for Alzheimer’s Disease (CERAD-plus, Chandler score), (2) depression: Geriatric Depression Scale, 15-item short form (GDS-SF), (3) social isolation: Lubben Social Network Scale-6-item form (LSNS-6), (4) psychological burden: Symptom Checklist-90®-Standard General Symptom Index (SCL-90®-S GSI), and (5) health-related quality of life: visual analogue scale of the EQ-5D.ResultsMild cognitive impairment was diagnosed in 11 participants with ARHL at baseline (39.3%). Only a minority exhibited psychological symptoms (n = 1–2, 3.6%–10.7% with pathological values in psychological outcomes). All primary outcomes failed to differentiate between hearing aid users vs. non-users over time (all interaction effects ns). At follow-up, between-group differences in psychological burden and quality of life were more pronounced in favor of hearing aid users vs. non-users.ConclusionARHL has a considerable impact on cognition. Whether hearing aid use is able to substantially attenuate cognitive impairment in a short term remains unclear. Further large-scale and long-term follow-up studies are needed to additionally address specific subgroups who might have more benefit from hearing aid use.Clinical Trial Registrationhttps://drks.de/search/de/trial/DRKS00025111, identifier DRKS00025111.